Chitosan Properties: A Preliminary Review - Othman, Siti Amira; Siti Nur Farahayu Abd Rahman (Journal of Advanced Mechanical Engineering Applications, 2024)
The content of amino groups in chitosan becomes the main cause of its differences from chitin in the context of structures and properties such as their chelation, flocculation, and biological functions. Furthermore, the random distribution of chitosan makes it easier to generate intra- and inter-molecular hydrogen bonds. Also, the existence of two hydroxyl groups and one primary amine group in chitosan, which can donate a free pair of electrons, make it soluble in diluted aqueous acetic solvents, and allow the formation of the coordination bonds that increase the possibilities for chemical modification. Its modification includes the incorporation of hydrophobic groups. Therefore, this paper reviews the properties of chitosan.